DEGRADASI LAHAN PADA SAWAH BEKAS PERTAMBANGAN BATU BATA DI KECAMATAN SALAMAN KABUPATEN MAGELANG TAHUN 2014 (SEBAGAI BAHAN PENGAYAAN DALAM PEMBELAJARAN GEOGRAFI PADA KOMPETENSI DASAR “MENGANALISIS SEBARAN BARANG TAMBANG DI INDONESIA BERDASARKAN NILAI S - Wulandari, Erni Latifah (Pendidikan Geografi, 2014)
ABSTRACTThe purposes of this study were: (1) determine the level of degradation which occurred in rice fields used brick mining in Salaman district (2) determine the level of productivity of paddy in rice field in Salaman District (3) determine the handling priority of rice field used brick mining in Salaman District (4) determine the implementation of land degradation in rice fields used brick mining in Geography learning in class XI of Senior High School.This study used qualitative methods with survey as the type of research. The approach used was spatial. The unit of analysis is a unit derived from an overlay of the Land Use Map, Soil Map, Slope Map, and excavation depth data, with the result was 10 land units. The technique of soil sampling used purposive sampling while the technique of respondent sampling was stratified purposive sampling. The techniques of data collection were field observation, interview, and documentation.The results of this study were: (1) Rice field degradation class in Salaman District consists of medium degraded land, which is 870.9 Ha (40.6%) on land units Sw-LC-I-0 and Sw-LC-I-30; low degraded land area, which is480.6 Ha (22.4%) on land units Sw-KLMK-II-0, Sw-KLMK-II-30, Sw-ACK-I-0, and Sw-ACK-I-30. (2) The decreasing of productivity between the origin land and the used brick mining land in the land units Sw-ACK-I-0 with Sw-ACK-I-30 worth of 281 kg/Ha, as well as on land Sw-LC- I-0 with Sw-LC-I-30 worth of 2597.4 kg/Ha. (3) Handling priority of rice field after brick mining in Salaman District consists of first priority on land units Sw-ACK-I-0, Sw-ACK-I-30 and Sw-LC-I-0, which is 1033.7 Ha (48.2%); Second priority on land units Sw-KLMK-II-0, Sw-KLMK-II-30, and Sw-LC-I-30, which is 317.7 Ha (14.8%). (4) The implementation of the land degradation in brick mining and the result map as a learning material for Geography learning in Class XI Senior High School Semester I. Keywords: Degradation, Fertility, Mining, Brick